From Classroom Exercises to Journal Publication: A Narrative Inquiry of Redesigning Arabic Writing Instruction - Khairani, Riska; Bahruddin, Uril; Arifa, Zakiyah; Faisal, Fasil (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study explores the pedagogical journey of redesigning Arabic writing instruction (Kitabah) from conventional classroom exercises toward a publication-oriented model. Employing a narrative inquiry approach, the research reconstructs the professional experiences of a senior professor at Universitas Islam Negeri Sumatera Utara through narrative interviews, researcher field notes, and document analysis. The findings reveal four transformative themes: (a) the strategic shift toward product-based learning, (b) the establishment of an intensive mentoring ecosystem with iterative revision cycles, (c) the cultivation of ethical awareness in journal selection, and (d) the enhancement of students' academic readiness and publication literacy. These themes converge to underscore the instructional model's transformative potential, evidenced by the successful publication of 12 student-authored articles in Sinta-indexed and Garuda-indexed journals within a single academic year. The discussion emphasises that this pedagogical transition necessitates the lecturer's evolution from a traditional evaluator into a rhythm regulator who fosters scholarly identity. Ultimately, this research demonstrates that integrating real-world publication standards into the curriculum proactively mitigates academic anxiety and empowers students as emerging scholars. The study offers a conceptual and ethical roadmap for language educators seeking to professionalise foreign-language pedagogy through intentional mentoring and rigorous scholarship.